2016
DOI: 10.17226/21852
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of Extreme Weather Events in the Context of Climate Change

Abstract: CoThis Ch subs wi Attribution ext of Climate Although the t and citations he National e s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
86
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(88 citation statements)
references
References 230 publications
(363 reference statements)
0
86
0
2
Order By: Relevance
“…This is due to a general increase in storminess in the same season during El Niño years when the polar jet stream flows farther south allowing more frontal systems to reach Florida (e.g., Douglas and Englehart 1981). The Pacific Decadal Oscillation (PDO) has a similar influence on Florida climate as ENSO, but on longer decadal time scales (Misra et al 2011). …”
Section: Floods and Climate Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to a general increase in storminess in the same season during El Niño years when the polar jet stream flows farther south allowing more frontal systems to reach Florida (e.g., Douglas and Englehart 1981). The Pacific Decadal Oscillation (PDO) has a similar influence on Florida climate as ENSO, but on longer decadal time scales (Misra et al 2011). …”
Section: Floods and Climate Variabilitymentioning
confidence: 99%
“…Future changes in precipitation extremes during the summer season are closely linked to changes in tropical cyclones (Misra et al 2011), as the latter contributes significantly to the number of extreme rainfall events observed throughout the state. For a high greenhouse gas emission scenario (Representative Concentration Pathway (RCP) 8.5) and the target year 2050, Gao et al (2012) found an increase of ~20% (302 mm/yr to 365 mm/yr) in the annual total of daily extreme precipitation, but smaller changes (~5% increase) in the frequency of daily extreme events.…”
Section: Outlooks Into the Futurementioning
confidence: 99%
“…Stakeholders from different sectors (insurance, policy making, media, legal) have a variety of different uses for such information . The US National Academy of Sciences recently assessed the validity of event attribution (NAS 2016) and concluded that Bit is now often possible to make and defend quantitative statements about the extent to which human-induced climate change (or another causal factor, such as a specific mode of natural variability) has influenced either the magnitude or the probability of occurrence of specific types of event or event classes.^The report noted that event attribution science Bhas advanced a great deal in recent years and is still evolving rapidly.^This was due to two main reasons: Bone, the understanding of the climate and weather mechanisms that produce extreme events is improving, and two, rapid progress is being made in the methods that are used for event attribution.D espite this progress, the approaches described above have been criticised for being flawed in two basic respects (Trenberth et al 2015;Mann et al 2017). First, it is argued that the reliance of event attribution studies on climate models makes standard approaches unreliable (Trenberth et al 2015).…”
mentioning
confidence: 99%
“…The second flaw, it is argued, is that standard event attribution approaches require significance testing in which the null hypothesis of no human influence must first be ruled out at a sufficiently high significance level (typically 5%) (Trenberth et al 2015;Mann et al 2017). Mann et al 2017 (see also Trenberth et al 2015) suggest that such a testing-based approach is Bconservative^and argue that an approach in which event likelihoods are estimated via Bayesian methods would be better both empirically and ethically.…”
mentioning
confidence: 99%
See 1 more Smart Citation